Arbitration in the Latin American Experience - Castillo Freyre, Mario (2008)
This paper analyzes the development of arbitration as an alternative means of conflict resolution in Latin America, especially since the 1990s. Latin America is in the process of transition: from romanticism to maturity, proof of this is the remarkable evolution that arbitration has had in recent years. Indeed, multiple countries have enacted laws directly oriented to this, others have enacted in the same law the regulation on mediation or conciliation and arbitration, in some cases regulated in two separate laws the regulation that regulates two of the main alternative methods according to each The country and many other countries have updated their legislation on arbitration. On the other hand, the author develops the differences between the arbitration of law and that of conscience, and establishes the model adopted in the different countries of Latin America: The separation of the arbitration of right of conscience, or also called arbitration of equity. In addition, the paper describes the situation of the arbitration with the State in Latin American countries, distinguishing two large blocks: i) Countries that have regulated by regulation the submission of the State to arbitration, such is the case of Guatemala, Costa Rica, Honduras, El Salvador, Ecuador, Bolivia and Paraguay. It should be noted that within this block is Peru and ii) Countries that do not contemplate regulation regarding this issue, such as Argentina, Uruguay and Mexico. However, in spite of the lack of homogeneity regarding the treatment of arbitration with the State in Latin America, the initiative of the countries in trying to involve the State in the use of arbitration is appreciated. Finally, the author develops the increase and expansion of institutional arbitration. During the last years, institutional arbitration has displaced institutional arbitration; this is mainly due to the new regulations that have been implemented.